In vitro Evaluation of Antimicrobial and Cytotoxic Activities of Rosmarinus officinalis L. (Lamiaceae) Essential Oil Cultivated from South-West Tunisia - Ines Ben Chobba, Ahmed Bekir, Riadh Ben Mansour, Noureddine Drira, Néji Gharsallah and Adel Kadri (Journal of Applied Pharmaceutical Science)
Rosmarinus officinalis (Lamiaceae), commonly known as rosemary and iklil, is often used by North African populations for the treatment of several inflammatory and infectious diseases. This study aimed to investigate the antimicrobial and cytotoxic properties of essential oil extracted from the seeds and leaves of R. officinalis. Antimicrobial activity assays involved the determination of inhibition zones and the minimum inhibitory concentration with regards to sixteen pathogenic microbial strains, using disc diffusion and minimum inhibitory concentration methods. The oil showed excellent activity against Staphylococcus aureus, followed by Staphylococcus epidermidis and Staphylococcus aureus 25923, with strong inhibition zones of 38.00, 29.40 and 26.00 mm, respectively. Cytotoxicity assays involved the application of an MTT testing method against HeLa cell lines. The results yielded high IC50 value values of up to 26,77 μg/ml. overall, the findings provided strong support for the strong candidacy of this plant for potential future application, particularly in the food and pharmaceutical industries, as a safe and cost-effective natural additive to substitute toxic synthetic food additives.
Keywords: Rosmarinus officinalis, essential oil, antibacterial activities, antifungal activities, activities, cytotoxic activities, HeLa cell lines.